Rhetoric and Guns - Skinnell, Ryan, 1978-; Kreuter, Nate; Wilkes, Lydia (Book collections on Project MUSE., 2022)
"Analyzes rhetoric about guns, guns in rhetoric, and guns as rhetoric, particularly as they relate to instances of guns in culture. Attempts to understand rhetoric's relationship to guns and how they function in and as rhetoric related to media coverage, political speech, marketing, and advertising"--